Numerical analysis of multirow arrangement of small diameter steel piles for landslide prevention - Mujah, Donovan; Ahmad, Fauziah; Hazarika, Hemanta; Watanabe, Naoto (Inpressco, 2013)
This paper intends to elucidate the prevention mechanism of small diameter steel piles (SDSP) and how multirow arrangement of the said piles affects the reinforced slope failure in landslide countermeasure. In this study, finite element analysis (FEA) employing Mohr-Coulomb’s elastic-perfectly plastic soil model was carried out to simulate the real condition in which, the effect of the varying ground densities (Dr=30% and Dr=80%) and cross sections (10 mm x 10 mm square and 3 mm in diameter piles) of the reinforcing rods in piles’ mechanism of landslide prevention were considered. Attempts also have been made to study the effect of introducing multiple rows arrangement of SDSP in terms of different cases of parametric study focusing on the effect of single, double and triple rows arrangements of those piles. Based on the results, it was observed that the shearing resistance in different pile cross sections is found to be significantly influenced by the variation of SDSP arrangement. However, irrespective of the piles arrangements, failure mode of a densely compacted ground is mainly governed by soil’s shearing resistance mobilized at a higher strain, while bending stiffness (EI) of the reinforcing material is more dominant in loose ground condition.